O poder moderador no Estado Brasileiro - Arthur Nadú Rangel (2019)
Looking at the history of independent Brazil until the current moment of the republic, the present master's research aims to delimit in a first moment the theory of Moderating Power through the clear French authors and the Brazilian scholars of such power in the imperial period, thus formulating a concept of Moderator Power that can be applied in the Brazilian State. In a second moment the research seeks to trace the trajectory of said Power in the Brazilian State in its two main moments: The Empire and the Republic. Demonstrating how the emperor acted as Moderator power and then observing the existence of this power in the Republic, through the action of the armed forces, which through the theory pointed out, assumed the role of Moderating Power acting in a clear way in the preservation of popular Sovereignty and in defense of the Brazilian State to the present day.